2007
DOI: 10.1093/pasj/59.sp1.s77
|View full text |Cite
|
Sign up to set email alerts
|

The Suzaku High Resolution X-Ray Spectrometer

Abstract: The X-Ray Spectrometer (XRS) has been designed to provide the Suzaku Observatory with non-dispersive, high-resolution X-ray spectroscopy. As designed, the instrument covers the energy range 0.3 to 12 keV, which encompasses the most diagnostically rich part of the X-ray band. The sensor consists of a 32-channel array of X-ray microcalorimeters, each with an energy resolution of about 6 eV. The very low temperature required for operation of the array (60 mK) is provided by a four-stage cooling system containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(59 citation statements)
references
References 62 publications
1
57
0
Order By: Relevance
“…This provided a stable 17 K interface temperature and a clean (i.e., no microphonics) environment for the He tank and the detector. Although LHe had evaporated one month after the launch due to a design problem (location of the He vent), initial data suggested very good thermal performance as a cooling system [4]. However, we also found that using two cryogens made the cooling system complicated, and ground operations hard to manage and risky.…”
Section: Design Conceptmentioning
confidence: 82%
See 3 more Smart Citations
“…This provided a stable 17 K interface temperature and a clean (i.e., no microphonics) environment for the He tank and the detector. Although LHe had evaporated one month after the launch due to a design problem (location of the He vent), initial data suggested very good thermal performance as a cooling system [4]. However, we also found that using two cryogens made the cooling system complicated, and ground operations hard to manage and risky.…”
Section: Design Conceptmentioning
confidence: 82%
“…1 and 2. The cooling chain from room temperature to the ADR heat-sink is composed of superfluid liquid 4 He, a 3 He JouleThomson (JT) cryocooler, and double-stage Stirling cryocoolers (hereafter 2ST). The starting point of the SXS cooling system design was that of the XRS.…”
Section: Design Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, the design of the SXS cooling system from room temperature to the ADR heat sink, which reflected many improvements resulting from the failure of the Suzaku x-ray spectrometer (XRS) 12 and lessons learned from it, is described. Details are described elsewhere.…”
Section: Designmentioning
confidence: 99%